Exploring Social Media Strategies For Enhancing Competitiveness In SMEs: A Case Study Of CV Wunggul Sejahtera Bersama - Chamid, Abdul; Irawan, Wahyu Purno; Emmywati, Emmywati (PRAGMATIS, 2025)
Small and Medium Enterprises (SMEs) are important contributors to the Indonesian economy, but many of them face challenges in maintaining competitiveness in the digital age. This study aims to explore how social media strategies can strengthen the competitiveness of SMEs by analyzing the case of CV Wunggul Sejahtera Bersama (WSB), a creative industry company in Surabaya. The approach used is qualitative with a single case study design. Data was collected through online observation, document analysis, and semi-structured interviews involving informants from internal parties (owners and marketing staff) and external parties (active followers of the company's social media). The data was analyzed using thematic analysis to identify patterns of digital engagement and effective communication strategies. The results of the study show that WSB's success in utilizing social media is influenced by perceptions of the usefulness and ease of use of technology, which encourages continuous innovation on platforms such as Instagram, Facebook, and TikTok. The integration of the Technology Acceptance Model (TAM) and the Resource-Based View (RBV) confirms that competitiveness stems not only from technological adoption, but also from creative abilities and the strategic utilization of internal resources.